Recent Advances in Grapes and Wine Production New Perspectives for Quality Improvement - Jordão, António M.; Botelho, Renato; Miljić, Uroš (IntechOpen, 2023)
Recent Advances in Grape and Wine Production - New Perspectives for Quality Improvement, written by a group of international researchers, provides a comprehensive overview of recent innovations in viticulture and enology - grape and wine production. This book is not only for technicians actively engaged in the field but also for students at technical schools and/or universities and other professionals interested in the latest innovations in grape and wine research.